US Raciolinguistics Heated Discourses: Can They be Brought to Indonesia? - Iqbal Nurul Azhar (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2022)
Raciolinguistics gained its momentum to grow fast when the Black Lives Matter (BLM) movement achieved its popularity in the United States. However, although the number of debates regarding raciolinguistic contributions to minimize racism acts among language experts in the United States has been continuously growing, this condition seems to have no significant impact on Indonesian linguistic study. From the library research, it has been found that even though the language racism issues, whether individual, communal and epistemic, are very common to be found in Indonesia, the attempts to bring raciolinguistics and language racism as a central discourse is so little. Indonesia has a multiracial society which makes this situation susceptible to disintegration without proper racism management. A survey published by the Washington Post newspaper puts Indonesia into the 5 most racist countries in the world and mentions 30-39.9 percent of Indonesia's citizens are racist. This survey is an indicator that racism might become a great issue for Indonesia. Based on this reason this article is presented. The article explains the background of the emergence of raciolinguitics, its development in the US, and the urgency of raciolinguistics to be developed in Indonesia. This article also describes some of the challenges that raciolinguitics might face in their efforts to introduce raciolinguitics in Indonesia.